Broken branches [compact disc] - Bentley, Dierks (Capitol Nashville, 2025)
Multiplatinum singer/songwriter Dierks Bentley has your back, dropping the grungy delight "She Hates Me." Landing somewhere between Whitley and Weezer, the new track features Bentley's patented style of country with a mischievous edge, plus the tongue-twisting story of a girl who is no longer falling for his country-boy charm. Millions of fans have connected to his songs featuring equal parts energy and emotion, and tastemakers around the nation continue to hail Bentley as one of country's most authentic entertainers.